2016
DOI: 10.1186/s12936-016-1142-8
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in children of Tshimbulu (Western Kasai, Democratic Republic of the Congo): epidemiological data and accuracy of diagnostic assays applied in a limited resource setting

Abstract: BackgroundThe literature data on malaria in Western Kasai, DRC, are limited and inadequate. A recent molecular survey there has detected Plasmodium ovale and Plasmodium malariae as mixed infections with Plasmodium falciparum. In Tshimbulu, Western Kasai, during a humanitarian initiative designed to provide children with free preventive screening and to reduce the local high malaria death rate, accurate species identification was performed, in order to collect unambiguous epidemiological data and to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Using a sub-set of 462 samples from the large, cross-sectional DHS, the prevalence of P. malariae and P. ovale among children in the DRC was found to be 12.9 and 8.3 %, respectively, with widespread geographical distributions seen in both species. A recent study of children in Western Kasai, DRC found a similar prevalence of P. malariae (13.8 %) but a lower prevalence of P. ovale (2.4 %) [ 14 ], and another study of asymptomatic individuals in six provinces of the DRC found a much lower prevalence of P. malariae (1.0 %) [ 15 ]. In 2007 prevalence were 4.9 % for P. malariae and 0.6 % for P. ovale [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a sub-set of 462 samples from the large, cross-sectional DHS, the prevalence of P. malariae and P. ovale among children in the DRC was found to be 12.9 and 8.3 %, respectively, with widespread geographical distributions seen in both species. A recent study of children in Western Kasai, DRC found a similar prevalence of P. malariae (13.8 %) but a lower prevalence of P. ovale (2.4 %) [ 14 ], and another study of asymptomatic individuals in six provinces of the DRC found a much lower prevalence of P. malariae (1.0 %) [ 15 ]. In 2007 prevalence were 4.9 % for P. malariae and 0.6 % for P. ovale [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mono-infection prevalence were only 1.0 and 0.6 %, respectively. In Western Kasai, there were no P. malariae or P. ovale mono-infections reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Na et al, 2014), while an imported babesiosis case involving co-infection with P. falciparum was previously described in the country (Ahn, 2010). Finally, in the Democratic Republic of Congo, coinfection with B. microti and P. falciparum has been diagnosed in minors with a prevalence of 1-6% (Gabrielli et al, 2016). Besides humans, cases of natural co-infection have also been described in closely related primate species; a macaque infected with a B. microti-like parasite exhibited suppressed P. cynomolgi infection (Wel et al, 2008), while co-infection in lemurs resulted in suppression of malaria infection and pathogenesis (Springer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These two countries alone, added to India, account for 40% of malaria cases [6]. In northeast DRC where Tshopo province is located, malaria is the cause of consultation in 37% of all pathologies and the cause of death at 30% of cases [4,5]. The equatorial facies which dominates this province in general and the city of Kisangani in particular and the presence of Plasmodium falciparum which ensures intense and permanent transmission as well as the insanitary condition of the environment would be the cause.…”
Section: Introductionmentioning
confidence: 99%